Simulasi Sistem Kontrol Berbasis IoT untuk Monitoring dan Pengusiran Hama Tikus di Lahan Pertanian - Oktaviani, Vina; Maruddani, Baso; Wahyu Iqbal, Muhamad (PENDIDIKAN VOKASIONAL TEKNIK ELEKTRONIKA FAKULTAS TEKNIK UNIVERSITAS NEGERI JAKARTA, 2024)
In the study of Internet of Things (IoT) Based Control System Simulation for Monitoring and Extermination of Rat Pests in Agricultural Land. The method used in this study is the simulation of rat movement, detection using PIR (Passive Infrared Sensor) connected to the LoRa Node, and sending to the LoRaWAN Gateway for sending to the cloud for the monitoring system. The detection data were analyzed using heatmaps and graphs of the number of detections per time for the installation of sensors and automatic traps. The simulation includes scenarios of node-gateway distance, antenna height, and vegetation density, as well as performance evaluation with confusion matrix metrics (TPR, FPR), latency, and trigger success. The results show stable motion detection with low latency at a coverage of hundreds of meters per gateway, while reliability increases significantly when the antenna is increased and the number of gateways is optimized. LoRa/LoRaWAN is proven to be adequate for low-power telemetry in agricultural land and is compatible with ecological-based rat control strategies.